TP53 germline testing and hereditary cancer: how somatic events and clinical criteria affect variant detection rate - Paula Rofes; Carmen Castillo-Manzano; Mireia Menéndez; Álex Teulé; Sílvia Iglesias; Elisabet Munté; Mireia Ramos-Muntada; Carolina Gómez; Eva Tornero; Esther Darder; Eva Montes; Laura Valle; et al. (Genome Medicine)
Abstract Background Germline heterozygous pathogenic variants (PVs) in TP53 cause Li-Fraumeni syndrome (LFS), a condition associated with increased risk of multiple tumor types. As the associated cancer risks were refined over time, clinical criteria also evolved to optimize diagnostic yield. The implementation of multi-gene panel germline testing in different clinical settings has led to the identification of TP53 PV carriers outside the classic LFS-associated cancer phenotypes, leading to a broader cancer phenotypic redefinition and to the renaming of the condition as “heritable TP53-related cancer syndrome” (hTP53rc). Germline TP53 variant interpretation is challenging due to the diverse nature of TP53 PVs, variable penetrance of the syndrome, possible occurrence of TP53 somatic mosaicism, and TP53 involvement in clonal hematopoiesis of indeterminate potential (CHIP). Here we aim to assess the relevance and impact of these issues on the diagnostic routine, and to evaluate the sensitivity of the different LFS clinical criteria to identify hTP53rc. Methods TP53 was analyzed in 6161 suspected hereditary cancer non-related patients categorized into three subgroups: (1) 495 patients fulfilling any LFS/Chompret clinical criteria; (2) 2481 patients diagnosed with early-onset breast/colorectal cancer; (3) 3185 patients without clinical criteria suggestive of hTP53rc. Ancillary tests were performed when TP53 PVs were identified in individuals not meeting LFS/Chompret criteria and/or when the variant was identified at low variant allele frequency (VAF). Results TP53 PVs were identified in blood DNA of 45 probands. Variant origin was elucidated in 39 of these: 72% patients had a constitutional PV, 10% were mosaics, and 18% had CHIP-associated PVs. Notably, two of the seven CHIP-TP53 PVs identified were detected at high allelic frequencies (VAF > 35%). Twenty-nine percent of germline TP53 PV did not meet any of the LFS clinical criteria. Among the clinical criteria, Chompret 2009 showed the highest sensitivity in our cohort (68% vs. 54% for Chompret 2015), highlighting the relevance of considering lung cancer in the criteria. Conclusions Our data supports performing TP53 ancillary testing for the identification of potential mosaicisms and CHIP-associated PVs, particularly in patients not meeting clinical criterial for LFS, irrespective of the VAF, and the application of clinical criteria that include lung cancer diagnosis.